Hydrofluoric acid-free wet etching liquid as well as preparation method and application thereof
Through the wet etching liquid without hydrofluoric acid, the combination of pure water, hydrochloric acid, hydrogen peroxide and nitric acid, the shortcomings in the etching rate and pattern clarity of the existing ferroelectric film material wet etching liquid are solved, and fast and efficient etching is achieved, ensuring the clarity of the etching pattern and the integrity of the edges, while in line with the concept of green and environmental protection.
Patent Information
- Application Number
- CN202510017513.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing wet etching liquid of ferroelectric film materials has disadvantages in terms of difficult to accurately control the graphic etching profile, poor clarity, slow etching rate and difficulty in regulation, easy failure of photoresist masks, and harmful to the environment and human health.
Provide a wet etching liquid without hydrofluoric acid, including purified water, hydrochloric acid, hydrogen peroxide and nitric acid. Through the mutual cooperation of these components, efficient etching of ferroelectric film materials can be achieved, ensuring the clarity of the etching profile and the regularity of the edges.
It realizes rapid and efficient etching of ferroelectric film materials, and the etching time is shortened to 10 to 100 seconds, which significantly improves production efficiency, ensures the clarity of the etching pattern and the integrity of the edges, and avoids the harm of hydrofluoric acid, which is in line with the concept of green and environmental protection.
Smart Images

Figure BDA0005230327100000081 
Figure BDA0005230327100000091 
Figure HDA0005230327110000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic material micro-processing, namely, wet etching solution in photolithography process, and specifically relates to a wet etching solution not containing hydrofluoric acid and a preparation method and application thereof. Background Art
[0002] Ferroelectric film materials, as a low-dimensional microelectronic functional material, have broad application prospects in the fields of sensors, actuators, memory, micro-electromechanical systems, etc. due to their various functional characteristics. In the preparation and micro-nano processing of ferroelectric film materials, in order to achieve their specific functions and precise structural construction, a variety of fine process technologies are indispensable, among which etching technology is an extremely critical micro-nano processing technology. Etching technology is a process that can selectively remove materials at the microscopic level. It can accurately remove specific areas of ferroelectric film materials according to pre-designed structural patterns, thereby shaping the microstructure and circuit layout that meet the requirements, laying the foundation for the effective application of ferroelectric film materials in various electronic devices.
[0003] Etching technology mainly covers two types: dry etching and wet etching. Although dry etching performs well in precise graphics and has good anisotropy, the equipment required is expensive, the etching rate is slow, and it takes a long time. In addition, it is easy to cause carbonization of the photoresist mask during the long etching process, making it difficult to effectively remove the photoresist later. In comparison, the wet etching process occupies an extremely important position in the field of high-precision micro-processing of materials due to its low raw material cost, fast etching rate, and excellent etching efficiency. This process mainly relies on the specific chemical reaction between the etching solution and the processed material to achieve the selective removal of specific areas of the material to construct the desired microstructure and device pattern.
[0004] However, the currently widely used wet etching solutions have exposed a series of serious problems in actual use, which greatly limits the further development of material micro-nano processing technology. First, many existing etching solutions often cannot achieve clear and definite pattern contours when etching ferroelectric film materials, and are prone to unnecessary lateral corrosion, which leads to the inability to accurately control the key dimensions of micro devices. Secondly, the etching rate of traditional ferroelectric film material etching solutions is generally low, usually several minutes or even tens of minutes. The long etching time not only means a significant reduction in production efficiency and increased production costs, but also introduces more process variables and uncertainties. Moreover, the long-term corrosion immersion of the etching material will cause permanent damage to the mask photoresist on its surface, causing the mask to fail, and the material in the non-target area will also be etched, ultimately causing damage to the device structure and loss of functional characteristics.
[0005] It is particularly noteworthy that many of the wet etching solutions for ferroelectric film materials currently used contain hydrofluoric acid (HF). Hydrofluoric acid is volatile and extremely corrosive and toxic. It poses a huge threat to the personal safety of operators during use. Even a trace amount of contact may cause severe skin burns and respiratory damage, endangering life. Therefore, hydrofluoric acid is subject to strict use controls. At the same time, waste liquid containing hydrofluoric acid is difficult to handle. If it is not handled properly, it will cause long-term and irreversible pollution to the ecological environment, which runs counter to the current global concept of green environmental protection and sustainable development.
[0006] Prior art, such as the Chinese invention patent with authorization announcement number CN 101381893 B, invented an etchant for CdGeAs2 crystals in order to avoid the use of volatile, corrosive and highly toxic hydrofluoric acid (HF) components, which is a mixture of hydrochloric acid, nitric acid and pure water in a volume ratio of 1:1:1. However, the etchant is targeted at specific CdGeAs2 crystals and the CdGeAs2 crystals must undergo very complex pre-etching sample treatments such as grinding and polishing, as well as high-temperature and long-term (40-60°C, at least 2 hours) sample drying treatments after corrosion. Moreover, the CdGeAs2 crystals need to be cleaned with an alkaline (such as sodium hydroxide) solution after corrosion, which greatly increases the time, cost and tediousness of the CdGeAs2 crystal corrosion process, and significantly reduces the industrialization efficiency. In particular, the patent cannot better control the corrosion rate of the CdGeAs2 crystals, nor can it accurately define the corrosion area of the CdGeAs2 crystals. Summary of the invention
[0007] The existing wet etching solution for ferroelectric film materials has drawbacks in that the etching profile of the pattern is difficult to be accurately controlled, the clarity is poor, the etching rate is slow and difficult to regulate, the photoresist mask is easy to fail, and it is harmful to the environment and human health. In view of the above-mentioned shortcomings of the existing wet etching solution for ferroelectric film materials, the present invention provides a wet etching solution without hydrofluoric acid and a simple preparation method thereof, so as to obtain an etching pattern of the ferroelectric film material with a clear profile and a high etching ratio.
[0008] In order to achieve the above object, the technical solution of the present invention is:
[0009] In a first aspect, the present invention provides a wet etching solution that does not contain hydrofluoric acid, which is used for wet etching of ferroelectric film materials, and includes pure water, hydrochloric acid, hydrogen peroxide and nitric acid, and does not contain hydrofluoric acid; the volume ratio of pure water: hydrochloric acid: hydrogen peroxide: nitric acid is (1-5): (1-10): (0.1-3): (0.1-3).
[0010] In some other embodiments, the mass concentration of the hydrochloric acid is 36-38%;
[0011] Or, the mass concentration of the hydrogen peroxide is 25-30%;
[0012] Or, the mass concentration of the nitric acid is 65-68%;
[0013] Alternatively, the pure water is one of ultrapure water, deionized water and distilled water.
[0014] In some other embodiments, the hydrochloric acid, hydrogen peroxide, and nitric acid are all of analytical grade.
[0015] The etching solution of the present invention does not contain highly toxic, volatile, and extremely corrosive hydrofluoric acid. The raw materials in the etching solution are cheap and easily available, and are easy to promote and apply. Hydrochloric acid is used as an etchant to etch the ferroelectric film, and pure water is used as a diluent to adjust the concentration of the etchant. Nitric acid is used to regulate the etching rate of the etching solution so that it exhibits good etching selectivity for the ferroelectric film material; hydrogen peroxide is used to protect the photoresist mask area, accurately define the etching area, and leave no residue in the etched area, thereby ensuring that the etching contour is regular and clear, and significantly enhancing the etching effect. Through the interaction between hydrochloric acid, hydrogen peroxide, nitric acid and pure water, a single ferroelectric film material (such as bismuth ferrite, barium titanate, lead zirconate titanate, strontium titanate film) or a multilayer ferroelectric composite film material (such as bismuth ferrite, barium titanate, lead zirconate titanate, strontium titanate, lanthanum nickelate multilayer composite film) on the surface of Si, SiO2 or Pt substrate can be cleanly, thoroughly and efficiently (only 10 to 100 seconds are required) at one time to obtain an etching pattern with complete and clear edges and almost no lateral corrosion.
[0016] In some other embodiments, the ferroelectric film material is a single film material or a multi-layer composite film material.
[0017] In some other embodiments, the single film material is one of bismuth ferrite, barium titanate, lead zirconate titanate, and strontium titanate thin films;
[0018] The multilayer composite film material is at least two of bismuth ferrite, barium titanate, lead zirconate titanate, strontium titanate, and lanthanum nickelate.
[0019] In a second aspect, the present invention provides a method for preparing the hydrofluoric acid-free wet etching solution described in the first aspect, comprising mixing pure water and hydrochloric acid evenly at room temperature, and then sequentially adding hydrogen peroxide and nitric acid and mixing evenly to obtain the wet etching solution.
[0020] In a third aspect, the present invention provides use of the hydrofluoric acid-free wet etching solution described in the first aspect in wet etching of ferroelectric film materials.
[0021] In a fourth aspect, the present invention provides a method for wet etching a ferroelectric film material, comprising the following steps:
[0022] (1) Spinning a photoresist on the surface of the ferroelectric film material to be etched, and after treatment, obtaining a ferroelectric film material with a patterned photoresist layer;
[0023] (2) etching the ferroelectric film material with the patterned photoresist layer in the wet etching solution without hydrofluoric acid described in the first aspect, and removing the etching solution remaining on the surface of the ferroelectric film material to obtain the etched ferroelectric film material;
[0024] (3) placing the etched ferroelectric film material in a photoresist stripping solution to strip the photoresist, and after removing the photoresist stripping solution, obtaining a ferroelectric film material containing a graphical etching pattern.
[0025] In some other embodiments, in step (1), the treatment is sequentially performed through pre-baking, exposure, post-baking, development and film hardening treatment.
[0026] In some other embodiments, in step (2), the etching temperature is 25 to 60° C., and the etching time is 10 to 100 seconds;
[0027] Or, in step (3), the photoresist stripping solution is one of acetone, dimethyl sulfoxide, N-methylpyrrolidone and N-ethylpyrrolidone, and the stripping time is 1 to 5 minutes.
[0028] Beneficial effects of the present invention:
[0029] 1. The hydrofluoric acid-free wet etching solution provided by the present invention does not contain any hydrofluoric acid component, is safer for personnel to operate, conforms to the concept of green environmental protection and sustainable development, and can reduce the difficulty and cost of waste liquid treatment, promote ecological balance, improve environmental quality and protect personal safety.
[0030] 2. The etching rate of existing ferroelectric film material etching solutions is generally low, usually several minutes or even tens of minutes. Too long etching time will cause permanent damage to the photoresist. The present invention provides a hydrofluoric acid-free wet etching solution and a preparation method thereof, with an etching time of 10 to 100 seconds. Compared with many other etching solutions, it has a higher etching rate and a higher etching ratio, which can significantly shorten the etching time and improve production efficiency.
[0031] 3. The wet etching solution provided by the present invention can accurately define the etching area in the micro-scale etching operation, and the etching boundary is clear and regular, which effectively avoids the edge blur and lateral corrosion problems often seen in traditional etching solutions. For devices, the etching pattern with clear contour edges ensures the precise control of the key dimensions of the microelectronic device, thereby helping to obtain a high-density integrated micro-device pattern.
[0032] 4. The etching solution provided by the present invention is prepared from pure water, hydrochloric acid, hydrogen peroxide and nitric acid. Its components and preparation method are simple, and the raw materials used are all conventional chemical reagents. They are easy to obtain and low in cost, which is conducive to large-scale industrial implementation.
[0033] 5. The etching solution provided by the present invention is applicable to a wide range of material systems and can etch a variety of film materials such as lanthanum nickelate, bismuth ferrite, barium titanate, lead zirconate titanate, and strontium titanate. The film material that can be etched can be a single film system of these film materials, or it can be a multilayer composite film system composed of these film materials, such as bismuth ferrite / lanthanum nickelate composite film, bismuth ferrite / barium titanate composite film, lead zirconate titanate / barium titanate composite film, barium titanate / strontium titanate composite film, bismuth ferrite / barium titanate / lanthanum nickelate composite film, barium titanate / bismuth ferrite / barium titanate composite film, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0035] Figure 1 Scanning electron microscope images of the surface patterning of the bismuth ferrite / lanthanum nickelate double-layer film sample before and after etching in Example 1 of the present invention, (a) before etching, (b) after etching;
[0036] Figure 2 This is a physical picture of the bismuth ferrite / lanthanum nickelate double-layer film sample after etching in half of the photoresist mask area in Example 1 of the present invention;
[0037] Figure 3 This is a scanning electron microscope image of the bismuth ferrite / lanthanum nickelate double-layer film sample after etching in Example 1 of the present invention;
[0038] Figure 4 The scanning electron microscope images of the barium titanate film material sample and the pattern after etching, (a) the actual image, (b) the pattern after etching;
[0039] Figure 5 The actual image of the lead zirconate titanate film material sample and the scanning electron microscope image of the pattern after etching, (a) the actual image, (b) the pattern after etching;
[0040] Figure 6 The actual image of the strontium titanate film material sample and the scanning electron microscope image of the pattern after etching, (a) the actual image, (b) the pattern after etching. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below through specific embodiments.
[0042] In the following examples, the raw materials are pure water, hydrochloric acid, hydrogen peroxide, and nitric acid, wherein the hydrochloric acid, hydrogen peroxide, and nitric acid are all of analytical grade, the mass concentration of hydrochloric acid is 36%, the mass concentration of hydrogen peroxide is 30%, and the mass concentration of nitric acid is 65%.
[0043] Example 1
[0044] A hydrofluoric acid-free wet etching solution is used to etch a bismuth ferrite / lanthanum nickelate double-layer composite film. The substrate used by the double-layer film is a silicon substrate with a metal platinum layer, that is, a bismuth ferrite / lanthanum nickelate / platinum / silicon system structure is formed. The bismuth ferrite film layer thickness in the double-layer film is about 100nm, and the lanthanum nickelate film layer thickness is about 300nm. It should be particularly noted that this embodiment is applicable to etching a single film material of bismuth ferrite or lanthanum nickelate, and the specific etching process is as follows:
[0045] (1) Preparation of etching solution
[0046] The wet etching solution for ferroelectric film materials without hydrofluoric acid is prepared from pure water, hydrochloric acid, hydrogen peroxide and nitric acid. The volume ratio of pure water: hydrochloric acid: hydrogen peroxide: nitric acid is 1:1:0.5:0.5, the mass concentration of hydrochloric acid is 36%, the mass concentration of hydrogen peroxide is 30%, and the mass concentration of nitric acid is 65%.
[0047] Pure water, hydrochloric acid, hydrogen peroxide and nitric acid are measured respectively according to the above volume ratio. At room temperature, the pure water and hydrochloric acid are first mixed evenly, and then hydrogen peroxide and nitric acid are added in sequence and mixed evenly to form a wet etching solution for ferroelectric film materials. The etching solution does not contain any hydrofluoric acid component.
[0048] (2) Photoresist coating on the surface of bismuth ferrite / lanthanum nickelate double-layer film
[0049] A photoresist film layer is uniformly coated on the surface of the bismuth ferrite / lanthanum nickelate double-layer film by a spin coating method, and then processed by pre-baking (110°C, 5 minutes), exposure (55 seconds), post-baking (120°C, 5 minutes), development (45 seconds), and hardening (130°C, 20 minutes) processes to obtain a patterned photoresist film layer.
[0050] (3) Etching of Bismuth Ferrite / Lannium Nickelate Double-layer Film
[0051] The bismuth ferrite / lanthanum nickelate double-layer film coated with the patterned photoresist is immersed in the etching solution prepared in step (1) at room temperature (about 25° C.) for 15 seconds, and then the residual etching solution is rinsed with deionized water and blown dry with nitrogen; then it is immersed in N-methylpyrrolidone (NMP) solution for 3 minutes to remove the photoresist on the surface of the bismuth ferrite / lanthanum nickelate double-layer film, so as to obtain the desired bismuth ferrite / lanthanum nickelate double-layer film etching pattern.
[0052] The surface of the etched bismuth ferrite / lanthanum nickelate double-layer film was observed using a scanning electron microscope. Figure 1 As shown, it can be seen that the square pattern of the membrane material sample after etching and degumming has a clear outline, very regular edges, and no lateral etching.
[0053] Figure 2 This is a photo of the bismuth ferrite / lanthanum nickelate double-layer film sample after etching half of the photoresist mask area. Figure 2 It can be seen that the bismuth ferrite / lanthanum nickelate double-layer film without a photoresist mask on the left side shows a bright area after etching, indicating that the bismuth ferrite / lanthanum nickelate double-layer film has been completely etched; the bismuth ferrite / lanthanum nickelate double-layer film with a photoresist mask on the right side still shows a complete area after etching, which is in sharp contrast to the area on the left, indicating that the photoresist has a good protective effect on the film material. Moreover, after etching, the boundaries of the left and right areas are clear and regular, which intuitively shows that the wet etching solution without hydrofluoric acid described in the present invention etches thoroughly without lateral etching.
[0054] Figure 3 for Figure 2 Scanning electron microscope image of the actual image of the bismuth ferrite / lanthanum nickelate double-layer film sample. The scanning electron microscope image more finely and clearly observes the difference between the left and right areas of the bismuth ferrite / lanthanum nickelate double-layer film sample after etching. This significant contrast difference is caused by the different film thicknesses on both sides; moreover, the boundary line between the two areas is very clear, which more fully demonstrates that the wet etching solution without hydrofluoric acid described in the present invention is accurate in etching and has no lateral etching.
[0055] Example 2
[0056] The difference from Example 1 is that in step (1), the volume ratio of pure water: hydrochloric acid: hydrogen peroxide: nitric acid is 1:5:1:1 or 1:5:1:2 or 1:5:2:1, and the other steps and process parameters are the same as those in Example 1.
[0057] Compared with Example 1, the hydrochloric acid content in the etching solution of pure water: hydrochloric acid: hydrogen peroxide: nitric acid = 1:5:1:1 in this embodiment is increased, and hydrochloric acid as an etchant will react more rapidly with the bismuth ferrite / lanthanum nickelate double-layer film, and the etching rate is faster. However, although the high hydrochloric acid content can significantly increase the etching rate, it is easy to cause lateral corrosion of the etching pattern and damage to the pattern photoresist, resulting in blurred and irregular pattern contours. Therefore, in this embodiment, the etching solution of pure water: hydrochloric acid: hydrogen peroxide: nitric acid = 1:5:1:2 or 1:5:2:1 ratio can compensate for the side effects of the high-content hydrochloric acid etching rate by adjusting the relative content of hydrogen peroxide and nitric acid. Nitric acid has a certain "passivation effect", which can make the etching rate of the etching solution milder and make its etching selectivity for ferroelectric film materials better; hydrogen peroxide has a strong oxidizing property, which can protect the photoresist mask area and improve the lateral corrosion problem of the etching solution, so as to ensure that the etching contour is regular and clear and enhance the etching effect.
[0058] Example 3
[0059] The difference from Example 1 is that the temperature of the etching solution in step (3) is 40° C., 50° C. or 60° C., and the other steps and process parameters are the same as those in Example 1.
[0060] Compared with Example 1, appropriately increasing the etching temperature of the etching solution during the etching process of the bismuth ferrite / lanthanum nickelate double-layer film helps the etching solution to react more completely and thoroughly with the bismuth ferrite / lanthanum nickelate double-layer film, significantly improving the etching rate, and more effectively etching the ferroelectric film material. If the temperature is too high, the evaporation of the etching solution will increase, which will weaken the etching efficiency of the etching solution; in addition, if the temperature is too high, the nitric acid and hydrogen peroxide components in the etching solution will oxidize the photoresist on the surface of the film material, making the photoresist difficult to remove. Therefore, the etching temperature of the wet etching solution not containing hydrofluoric acid described in the present invention is preferably room temperature to 60°C.
[0061] Example 4
[0062] The difference from Example 1 is that the etching time in step (3) is 30 seconds, 50 seconds or 90 seconds, and the other steps and process parameters are the same as those in Example 1.
[0063] Compared with Example 1, the etching time of the bismuth ferrite / lanthanum nickelate double-layer film in this embodiment is prolonged. Properly prolonging the etching time helps the etching solution to react with the bismuth ferrite / lanthanum nickelate double-layer film to be more complete and thorough, and the etching area is clean and free of residue. If the etching time is too long, the ferroelectric film material will be lateral-corroded, resulting in a blurred and irregular etching profile; in addition, if the etching time is too long, the etching solution will damage the photoresist on the surface of the film material, making it difficult to remove the photoresist and difficult to protect the ferroelectric film material well. Therefore, the preferred etching time of the hydrofluoric acid-free wet etching solution and its preparation method and application described in the present invention is 15 to 90 seconds.
[0064] Example 5
[0065] The difference from Example 1 is that the photoresist stripping solution in step (3) is acetone or dimethyl sulfoxide (DMSO) or N-ethylpyrrolidone (NEP), and the other steps and process parameters are the same as those in Example 1.
[0066] The acetone or dimethyl sulfoxide (DMSO) or N-ethylpyrrolidone (NEP) photoresist stripping solution provided in this embodiment can remove the photoresist film layer on the surface of the bismuth ferrite / lanthanum nickelate double-layer film. Taking into account the stripping rate and effect of the photoresist, the present invention discloses a hydrofluoric acid-free wet etching solution and its preparation method and application, wherein the preferred photoresist stripping solution is N-methylpyrrolidone (NMP) or acetone.
[0067] Example 6
[0068] Different from Example 1, the ferroelectric film material wet etching solution that does not contain hydrofluoric acid is used for a single film material system of barium titanate, lead zirconate titanate and strontium titanate, or a multilayer composite film system composed of these thin film materials. The specific etching time depends on the composition of the film material system and the thickness of the film layer. The other steps and process parameters are the same as those in Example 1.
[0069] Figure 4 The figure is a real picture of a barium titanate film material sample and a scanning electron microscope picture of the pattern after etching, indicating that the etching solution of the present invention can effectively etch the barium titanate film material.
[0070] Figure 5 The figure is a physical picture of a lead zirconate titanate film material sample and a scanning electron microscope picture of a pattern after etching, indicating that the etching solution of the present invention can effectively etch the lead zirconate titanate film material.
[0071] Figure 6 The actual image of the strontium titanate film material sample and the scanning electron microscope image of the pattern after etching indicate that the etching solution of the present invention can effectively etch the strontium titanate film material.
[0072] The above etching results show that the hydrofluoric acid-free wet etching solution prepared in Examples 1 to 6 has an excellent etching effect on ferroelectric film materials.
[0073] Comparative Example
[0074] Compared with Example 1, the preparation components and component ratios of the etching solution in step (1) are different, the immersion time (etching time) of the bismuth ferrite / lanthanum nickelate double-layer film in the etching solution in step (3) is different, and the other steps and process parameters are the same as those in Example 1.
[0075] The following table shows the etching conditions of the bismuth ferrite / lanthanum nickelate double-layer film material in Example 1 using etching solutions of different components and ratios in Comparative Examples 1-6 as shown in Table 1. Among them, the mass concentration of the hydrofluoric acid used is 40%, the mass concentration of the sulfuric acid used is 95%, and the purity level is analytically pure, and the mass concentrations of other solutions used are the same as those in Example 1.
[0076] Table 1 Etching of bismuth ferrite / lanthanum nickelate double-layer film materials by etching solutions with different components and ratios
[0077]
[0078]
[0079] As can be seen from Table 1, compared with Example 1, the etching effect of the etching solution in this comparative example on the ferroelectric film material is not ideal. Specifically, the etching solution of Comparative Example 1 can completely etch the bismuth ferrite / lanthanum nickelate film material, but no matter how the component ratio is adjusted, the etching time is short, the etching rate cannot be well controlled, and the complete pattern cannot be etched. The etching solution of Comparative Example 2, no matter how the etching time is adjusted and the component ratio is adjusted, the photoresist is destroyed and the lanthanum nickelate layer cannot be etched. The etching solution of Comparative Example 3, no matter how the etching time is adjusted and the component ratio is adjusted, the photoresist is destroyed and the bismuth ferrite / lanthanum nickelate double-layer film material cannot be etched. The etching solution of Comparative Example 4, the bismuth ferrite / lanthanum nickelate double-layer film material can be etched, but no matter how the etching time is adjusted and the component ratio is adjusted, the photoresist is easily destroyed, the double-layer film shows some lateral etching, and the etching profile lacks clear rules. In the etching solution of Comparative Example 5, the bismuth ferrite / lanthanum nickelate double-layer film material can be etched, but the etching rate is slow, there are some residues in the etched area, and the etching profile is not clear. In the etching solution of Comparative Example 6, regardless of the etching time, the photoresist is destroyed and the bismuth ferrite / lanthanum nickelate double-layer film material cannot be etched.
[0080] This shows that the hydrofluoric acid-free wet etching solution and its preparation method described in Examples 1 to 6 of the present invention have good etching effect on ferroelectric film materials, the edges of the etched pattern contours are regular and clear, and there is no lateral corrosion; and the etching solution and its preparation method are suitable for a variety of ferroelectric film materials, and can be used for single film material systems of lanthanum nickelate, bismuth ferrite, barium titanate, lead zirconate titanate, strontium titanate, etc., or a multilayer composite film material system composed of these film materials.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A wet etching solution free of hydrofluoric acid, characterized in that: The invention is used for wet etching of ferroelectric film materials, comprising pure water, hydrochloric acid, hydrogen peroxide and nitric acid, but excluding hydrofluoric acid; the volume ratio of the pure water: hydrochloric acid: hydrogen peroxide: nitric acid is (1-5): (1-10): (0.1-3): (0.1-3).
2. The hydrofluoric acid-free wet etching solution according to claim 1, characterized in that: The mass concentration of the hydrochloric acid is 36-38%; Or, the mass concentration of the hydrogen peroxide is 25-30%; Or, the mass concentration of the nitric acid is 65-68%; Alternatively, the pure water is one of ultrapure water, deionized water and distilled water.
3. The hydrofluoric acid-free wet etching solution according to claim 1, characterized in that: The hydrochloric acid, hydrogen peroxide and nitric acid are all of analytical grade.
4. The wet etching solution not containing hydrofluoric acid according to claim 1, characterized in that: The ferroelectric film material is a single film material or a multi-layer composite film material.
5. The hydrofluoric acid-free wet etching solution according to claim 4, characterized in that: The single film material is one of bismuth ferrite, barium titanate, lead zirconate titanate and strontium titanate thin films; The multilayer composite film material is at least two of bismuth ferrite, barium titanate, lead zirconate titanate, strontium titanate, and lanthanum nickelate.
6. A method for preparing a hydrofluoric acid-free wet etching solution according to any one of claims 1 to 5, characterized in that: At room temperature, mix pure water and hydrochloric acid evenly, then add hydrogen peroxide and nitric acid in sequence and mix evenly to obtain the product.
7. Use of the hydrofluoric acid-free wet etching solution according to any one of claims 1 to 5 in wet etching of ferroelectric film materials.
8. A method for wet etching of a ferroelectric film material, characterized in that: The following steps are involved: (1) Spinning a photoresist on the surface of the ferroelectric film material to be etched, and after treatment, obtaining a ferroelectric film material with a patterned photoresist layer; (2) etching the ferroelectric film material with the patterned photoresist layer in the wet etching solution without hydrofluoric acid as claimed in any one of claims 1 to 5, and removing the etching solution remaining on the surface of the ferroelectric film material to obtain the etched ferroelectric film material; (3) placing the etched ferroelectric film material in a photoresist stripping solution to strip the photoresist, and after removing the photoresist stripping solution, obtaining a ferroelectric film material containing a graphical etching pattern.
9. The method for wet etching of ferroelectric film material according to claim 8, characterized in that: In step (1), the treatment is sequentially performed through pre-baking, exposure, post-baking, development and film hardening treatment.
10. The method for wet etching of ferroelectric film material according to claim 8, characterized in that: In step (2), the etching temperature is 25 to 60° C., and the etching time is 10 to 100 seconds; Or, in step (3), the photoresist stripping solution is one of acetone, dimethyl sulfoxide, N-methylpyrrolidone and N-ethylpyrrolidone, and the stripping time is 1 to 5 minutes.
Citation Information
Patent Citations
CdGeAs2 crystal etching agent and etching method
CN101381893B
Novel etching solution used in oxide material system, and etching method and application thereof
CN103980905A
Corrosive liquid for accurately controlling micro metal Ni mask pattern and use method
CN115679326A
Method for cleaning PZT thin film
CN1241457A
Titanate dissolving liquid and dissolving method
JP1996310887A